ASSESSMENT OF DIAGNOSTIC ACCURACY OF TRANS-ABDOMINAL ULTRASOUND IN DIAGNOSIS OF CHOLEDOCHOLITHIASIS KEEPING MAGNETIC RESONANCE CHOLANGIO-PANCREATOGRAPHY AS GOLD-STANDARD (The Research of Medical Science Review, 2025)
Objectives: To assess the diagnostic accuracy of TAUS in detecting choledocholithiasis, using MRCP as the gold standard. Methodology: The study conducted at Radiology and Imaging Department, Al-Noor Diagnostic Center, Lahore, Pakistan during the period May 2, 2024 to November 2, 2024. This cross-sectional study included 248 patients aged 18–85 years presenting with clinical suspicion of choledocholithiasis. TAUS and MRCP findings were compared. Diagnostic accuracy was calculated using MRCP as the reference. Results: Among 248 patients, 62.5% were female and 56.5% were below 50 years. TAUS detected choledocholithiasis in 20.2% cases, while MRCP confirmed it in 28.6%. TAUS showed a sensitivity of 54.9%, specificity of 93.8%, positive predictive value of 78%, negative predictive value of 83.8%, and overall diagnostic accuracy of 82.7%. Detection was notably lower in small or distal stones. Conclusion: TAUS demonstrates high specificity and reasonable diagnostic accuracy for detecting choledocholithiasis and should be employed as the first-line investigation, especially in low-resource settings. When TAUS results are inconclusive, MRCP should be pursued. Structured imaging protocols and trained operators may further enhance TAUS performance.